Study on stability differences in heel kick movements of Tai Chi athletes based on statistical parametric mapping - Zhang, Xiaopei; Liu, Gan; Jia, Mengyao; Ma, Yong (Frontiers in Physiology, 2025)
ObjectiveThe study aims to investigate the stability differences in the heel kick movement between Tai Chi athletes of different skill levels and explore the impact of Tai Chi training on postural control and stability.MethodsThe study recruited 16 Tai Chi athletes, who were divided into two groups based on their skill level: the Elite Group (EG, 8 athletes) and the Sub-Elite Group (SG, 8 athletes). While performing the heel kick movement, the athletes’ kinematic data were captured using a Vicon motion capture system. The study compared the differences between the two groups by analyzing the changes in hip, knee, and ankle joint angles, and by using the SPM method. Additionally, the inter-group differences in center of mass (CoM) sway volume were also compared.ResultsSignificant differences in joint angles were observed, with EG showing greater stability in knee and ankle external rotation. During the knee-lifting phase, the CoM sway volume of the EG was significantly greater than that of the SG (p = 0.046), indicating larger postural adjustments in EG during this stage. No significant differences were found in the extension and recovery phases (p > 0.05).ConclusionEG demonstrate superior joint stability and more efficient postural control strategies during the heel kick, particularly in the preparation phase. These findings highlight the role of advanced neuromuscular coordination in enhancing movement stability, providing biomechanical evidence to inform high-performance Tai Chi training.